Diabetes Mellitus and Periodontitis: Relevance of the Diabolic Duo in India - Sumidha Bansal; Sangeeta Dhir; Subhash Kumar Wangnoo (Apollo Medicine)
Diabetes and periodontitis are highly prevalent diseases. Chronic nature, along with shared risk factors, magnifies the complexity of both the diseases. Periodontal treatment results in clinically relevant reductions in HbA1c, and the presence of diabetes worsens the periodontal health and vice-versa. This paper presents an overview on the pathogenic mechanisms, impact of intervention, and significance of interprofessional collaborations for holistic management in diabetes and periodontitis.